THE RITE OF CIRCUMCISION AMONG THE PEOPLES OF THE CAUCASUS - Musaeva, Majsarat Kamilovna; Solov'eva, Lubov' Timofeevna (History, Archeology and Ethnography of the Caucasus, 2022)
For the peoples of the Caucasus, ritual culture, the preservation of family and household traditions and the family well-being associated with them have been and remain the most significant life values. One of the important traditions, which is strictly observed by the majority of the peoples of the Caucasus who profess Islam, is circumcision – “sunnat/sunnet”. The authors attempt to consider and analyze this tradition, which in the Caucasian ethnography has been studied episodically. The authors aim to demonstrate the variety of the tradition, its role in the family and social rituality of different regions of the Caucasus, the dynamics of its transformation; to provide a clearer picture about the importance of such a family-social ritual in traditions of those Caucasians, who practiced it. The article describes the ritual complex, beliefs, omens, rites, that accompanied this important ceremony, and analyses the common and particular aspects in the regional diversity among the peoples of the Caucasus. In the course of our study, we applied a systematic approach – the study of family customs and rituals in conjunction with other aspects of traditional culture (social life, religious beliefs, ritual culture) and a historical and comparative method – material was obtained on different peoples of the Caucasus in order to identify common patterns and distinctive features. The methodological and theoretical basis for writing the article was the research of Caucasian scholars, thanks to which its authors identified the most interesting points regarding the ritual culture related to the subject of the study.
Keywords: peoples of the Caucasus; North Caucasus; Dagestan; circumcision; sunnatchi/sunnetchi; gender identification; initiation; socio-marking rituals